Upper Ordovician (Hirnantian) to lower Silurian (Aeronian) graptolite biostratigraphy of the Dingjiapo section, Hubei Province, China and its implications - Jörg Maletz; Chuanshang Wang; Xiaofeng Wang (PalZ, 2026)
The graptolite faunas of the late Katian (Upper Ordovician) Paraorthograptus pacificus Biozone and the Hirnantian (Upper Ordovician) Metabolograptus persculptus Biozone to the Silurian (Llandovery) Lituigraptus convolutus Biozone are recognized in the Dingjiapo section of Hubei Province, China. The Rhuddanian to mid-Aeronian succession appears to be at least highly condensed. Thus, the Coronograptus cyphus to the Pribylograptus leptotheca Biozone intervals have not been recognized and have to be interpreted as lacking due to the strong condensation of the succession or the presence of a sedimentological gap. Metaclimacograptus sculptus appears in unit HDS-6 with a rich graptolite fauna of the lower Lituigraptus convolutus Biozone, while the underlying unit HDS-5 bears a fauna of the Cystograptus vesiculosus Biozone of mid-Rhuddanian age. The highest part of the successions is referred to the Metaclimacograptus sculptus Subzone of the Lituigraptus convolutus Biozone. A gap at the Rhuddanian–Aeronian boundary has been recognized in a number of sections in the region SE of the Huangling Massif and, thus appears to be a regional feature useful for the paleogeographic interpretation of the region.